2016
DOI: 10.1002/chem.201505042
|View full text |Cite
|
Sign up to set email alerts
|

Formation of N‐Heterocyclic Carbenes by Tautomerization of Mesomeric Betaines: Cyclic Boron Adducts and Palladium Complexes From 2‐(Imidazolium‐1‐yl)phenolates

Abstract: 2-(Imidazolium-1-yl)phenolates are conjugated heterocyclic mesomeric betaines in tautomeric equilibrium with the corresponding N-heterocyclic carbenes (NHCs), 3-(2-hydroxyphenyl)-imidazol-2-ylidenes. The carbene tautomers can be trapped as thiones (X-ray analysis). Moreover, bis(triphenylphosphine)palladium(II) dichloride in THF trapped the carbene tautomer as a palladium complex without participation of the phenolate group (X-ray analysis). The corresponding anionic NHCs, 2-phenolate-substituted imidazol-2-yl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 92 publications
0
7
0
1
Order By: Relevance
“…Salt 5 is available via a three-step procedure [35]. Deprotonation with potassium carbonate resulted in the formation of the tautomeric equilibrium of the mesomeric betaine 6A and its NHC 6B (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salt 5 is available via a three-step procedure [35]. Deprotonation with potassium carbonate resulted in the formation of the tautomeric equilibrium of the mesomeric betaine 6A and its NHC 6B (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of lithium 2-(3-butyl-1 H -imidazol-2-ylidene-1-yl)phenolate (7): A solution of 0.02 g (0.09 mmol) of 2-(3-butyl-1 H -imidazolium-1-yl)phenolate [35] and 0.10 mL of lithium bis(trimethylsilyl)amide (1.0 M solution in THF) in 0.7 mL of pyridine was stirred for 30 minutes at rt. The product was characterized in solution, as traces of moisture reconstituted the starting material.…”
Section: Methodsmentioning
confidence: 99%
“…Other examples of conjugated systems with related structures have been described as well. [24][25][26][27][28][29][30][31][32] Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Nitron belongs to the class of conjugated mesomeric betaines (CMBs) [ 34 ]. Related work on other five-membered CMBs in equilibrium with their tautomeric NHCs was published by the groups of César and Lavigne [ 35 , 36 , 37 ], Braunstein and Danopoulos [ 38 , 39 , 40 ], Ganter [ 41 ] and Schmidt [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], who also provided the first review of this burgeoning field [ 50 ]. We demonstrated that the electronic properties of 2 ′ are very similar to those of the “Enders carbene” ( 1 ) [ 31 , 32 , 33 ], as is reflected by their essentially identical Tolman Electronic Parameter (TEP) values [ 51 ] as well as by the very similar 77 Se NMR chemical shift values (∆δ = 4 ppm) determined for their corresponding selenone derivatives.…”
Section: Introductionmentioning
confidence: 99%